Assessing participatory budgeting in an executive dominated state : the case of Botswana - Mokaloba, M.; Molokwane, T.; Motshegwa, B. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
Botswana has been hailed as a shining example of democracy in multiple fora across the globe. This made the country one of the limited examples of countries with good governance practices in a continent commonly associated with autocratic and authoritarian regimes characterised by inter alia, intra and interstate conflicts. A close inspection of some of the administrative processes of the state supports this narrative but on the contrary, the executive has been labelled dominant over other arms of the government. The significance of public finance and budgeting processes places the same as one of the most critical elements to establishing the extent of democracy and participation in a nation state. This is largely borrowed from the roots of participatory budgeting in Porto Allergre, Brazil and has since been incorporated as one of the key aspects of democratic governance. Against this background, this paper assesses the inclusiveness and participation levels of the citizenry in Botswana. The study uses desk research and draws information from published materials such as books journals, newspapers and at the same time relying on official government documents and other secondary sources of information. In Line with democratic principles and performance as well as people-oriented-budgeting, this article also establishes how Botswana fares in incorporating these into its budget cycle on the basis of the dominance of the executive. The paper confirms that the government of Botswana is largely dominated by the executive and that is the case in administrative and political processes such as the budgetary process. The paper nonetheless, points out a number of the initiatives some old and some new, developed to ensure that the budgetary process is inclusive of other actors like citizens. In conclusion, a number of weak links such as the executive having to exclude other actors from the budgetary process are identified and recommendations to the same are provided for purposes of advising public policy.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Botswana; Democracy; Executive; Participatory budgeting; State; Democracy -- Botswana; Budgeting -- Botswana